Visualisasi Dan Identifikasi Pola Retak Dinding Bata Akibat Penurunan Pondasi Struktur Bangunan Di Kota Banjarmasin - Tjitradi, Darmansyah; Eliatun, Eliatun (Jurnal Teknik Sipil, 2018)
The City of Banjarmasin has very low soil bearing capacity leading to a significant number of buildings experiencing foundation settlement. This causes many elements of the buildings to develop cracks and to lean. The foundation settlement is modelled using ANSYS by taking five building structure models with brick walls loaded with their selves weight. Through this modelling the crack pattern and the stress distribution on both walls and the structural elements can be visualised and identified. The results show that the following columns experiencing foundation settlement develop longitudinal cracks, crack patterns on brick walls are diagonal at every bottom corner of the columns and vertical at the edge of the inner columns if there is no foundation settlement. Crack patterns on brick walls take form of a letter V if only one or two outer column experience foundation settlement, and crack patterns on brick walls also take form of an inverted letter V if only the inner columns or two adjacent columns experience foundation settlement. Foundation settlement experienced by inner columns of a brick wall is a major cause of damage to structural components.